Undergraduates’ speaking anxiety in English as second language (ESL) classrooms / Kimberley Lau Yih Long, Yeo Jiin Yih and Sandra Sim Phek Lin - Yih, Kimberley Long Lau; Yeo, Jiin Yih; Sim, Sandra Phek Lin (Universiti Teknologi MARA Cawangan Sarawak, 2019)
Many students exhibit fear of speaking in English in the English as Second Language (ESL) classrooms. Additionally, there are limited studies in this area of concern among the undergraduates in Sarawak. Hence, this study aimed to identify the students‟ anxiety level towards speaking English based on four components, namely communication apprehension, test anxiety, fear of negative evaluation, and comfort in using English in the classrooms. This study also examined whether there is any significant difference in the level of anxiety in terms of gender. A total of 592 undergraduates from two public institutions of higher learning in Sarawak were involved in this study. A Public Speaking Class Anxiety Scale (PSCAS) by Yaikhong and Usaha (2012) was adopted in this study to measure anxiety in the ESL speaking classes. The results gathered through the questionnaires were analysed using SPSS package to determine the students‟ speaking anxiety levels and the significant difference in the level of anxiety in speaking English in terms of gender. Thefindings revealed that undergraduates experienced an average level of speaking anxiety. T-test analysis of the findings in the study also portrayed that generally the female undergraduates experienced higher speaking anxiety as compared to the male undergraduates in all the four factors of ESL speaking anxiety. Among the four factors of speaking anxiety, only the factor of „comfort in using English‟ in the classrooms showed a statistically significant difference between male and female undergraduates. Findings of this study would be significant as knowing the level of anxiety among the undergraduates in ESL classrooms will provide the basis for educators to plan better strategies or techniques to help students in overcoming their English speaking anxiety and to improve their oral English proficiency. It will also help students to be aware of their own speaking anxiety level so that they can seek for measures to overcome their speaking anxiety.